Pengaruh Kebijakan Pemerintah terhadap Keberhasilan Digitalisasi Pendidikan di Negara Berkembang - Muhammad Juliansyah Putra; Caroline, Caroline; St. Wijdanah Ram (Jurnal Ilmiah Edukatif, 2025)
This study examines the influence of government policy on the success of education digitalisation in developing countries. The study uses a literature review method. The results show that government regulation and investment play an important role in improving the accessibility of educational technology, especially in remote areas. Policies that focus on providing adequate infrastructure, such as internet access and hardware, are key factors in facilitating the digitalisation of education. In addition, teacher training and competency development are important aspects that need attention to ensure that technology can be effectively integrated into the learning process. The importance of inclusive policies is also emphasised to reduce the digital divide through device subsidies and internet fee assistance programmes to ensure equal access for all students. In conclusion, comprehensive and well-planned government policies can encourage the successful digitalisation of education and improve the quality of education in developing countries.